Impact of urease inhibitor on greenhouse gas emissions and rice yield in a rainfed transplanting rice system in Costa Rica - Giraldo-Sanclemente, Weynner; Pérez-Castillo, Ana Gabriela; Monge-Muñoz, Mayela; Chinchilla-Soto, Cristina; Chavarría-Pérez, Lourdes; Alpízar-Marín, Melvin; Zaman, Mohammad (Frontiers in Agronomy, 2025)
Rice crop production intensification has become one of the most important sources of greenhouse gases. In rainfed rice production, urea is the most common nitrogen (N) fertilizer used in Costa Rica. Urea has low efficiency in crops, which is associated with high risk of N gaseous losses. The use of urea coated with the urease inhibitor NBPT has been identified as a mitigation strategy for ammonia losses. However, this can increase N input to the system, potentially leading to higher N2O and CH4 emissions in rice fields. In 2022, a rainfed rice transplanting trial was conducted on a tropical Inceptisol in Costa Rican Central Pacific region to analyze yield and quantify N2O and CH4 emissions. The plots of 6m x 6m, with an experimental design of five complete randomized blocks, were treated with three N-fertilization treatments: urea (U; 144 kg N ha−1), urea plus NBPT (UI; 144 kg N ha−1) and control plots (without N). Total N was splitted in four applications. The yield did not exhibit a significant difference (p>0.05) between U and UI treatments (U: 5.72 ± 0.97 t ha−1, and UI: 5.86 ± 1.12 t ha−1). There were no significant differences in yield-scaled N2O emissions (U: 4.4 ± 1.9 ug N2O-N kg−1rice, UI: 4.2 ± 1.9 ug N2O-N kg−1rice) or yield-scaled CH4 emissions (U: 0.32 ± 0.20 mg CH4 kg−1rice, UI: 0.33 16 ± 0.18 mg CH4 kg−1rice). Environmental factors and soil conditions such as temperature, pH, clay content, and specific cation exchange capacity could reduce the efficacy of NBPT. Under the experimental conditions, NBPT did not promote economic benefits, nor did it have an impact on greenhouse gas emissions.